Tin Coatings Electrodeposited from Sulfonic Acid-Based Electrolytes : Tribological Behavior - Bengoa, Leandro Nicolás (2015)
A high efficiency methane sulfonic acid electrolyte used for tin electrodeposition was studied, and the properties of the resulting deposits were compared to those of tin coatings obtained from an industrial phenol sulfonic acid electrolyte. Cyclic voltammetry was used to study the effect of organic additives on the reduction process to define the composition of the electrolytic bath. Thick tin electrodeposits were obtained on rotating cylinder steel electrodes, and their surface morphology, preferred crystal orientation, surface roughness, micro hardness, and tribological behavior were measured. Smooth, adherent, and bright tin coatings were obtained from the methane sulfonic acid electrolyte, which differed in morphology and texture from tin electrodeposited from the industrial bath. Influence of organic additives on preferred crystal orientation of the coatings was found to be stronger than changing the supporting sulfonic acid type. Tribological tests showed that the two types of deposits have a similar coefficient of friction. However, tin coatings obtained from methane sulfonic electrolytes presented a lower wear resistance and underwent galling at lower loads.